Endoscopic findings and esophageal cancer incidence among Fanconi Anemia patients participating in an endoscopic surveillance program. Issue 2 (February 2019) - Itskoviz, David; Tamary, Hannah; Krasnov, Tanya; Yacobovich, Joannae; Sahar, Nadav; Zevit, Noam; Shamir, Raanan; Ben-Bassat, Offer; Leibovici Wiseman, Yaara; Dickman, Ram; Ringel, Yehuda; Dotan, Iris; et al.
Abstract: Background and aims: The primary clinical characteristics of Fanconi Anemia (FA) include typical physical features, progressive bone marrow failure, and an increased incidence of neoplasms, including esophageal carcinoma. Currently, there are no data regarding endoscopic findings or the interval time to malignancy in these patients. Data about the contribution of Human Papilloma Virus (HPV) to esophageal carcinoma is conflicting. Our objective is to document the upper gastrointestinal (GI) findings at baseline, document cancer incidence, and evaluate the role of HPV among these cancers. Methods: We reviewed endoscopic and clinical data of FA subjects who participated in active surveillance before cancer diagnosis. Incident esophageal cancers were stained for HPV p16 protein. Results: Eight FA patients were included (men 62.5%; median age at first endoscopy 20 years, median endoscopies number: 5.5). At baseline, 8/8 had endoscopic evidence for reflux esophagitis. In 3/8 the reflux esophagitis was mild and in 5/8 it was moderate or severe. During the follow up time (median time 4.5 years 2/8 developed Barrett's esophagus and 2/8 patients had incident esophageal squamous cell carcinoma during follow up, at intervals of eight and eighteen months from the previous upper endoscopy. Both cancers stained negative for HPV P16 . Conclusions: FA subjects have both an extremely high risk for esophageal cancer within short intervals and a very high prevalence of reflux esophagitis with various severities. Active surveillance programs in specialized centers including annual upper endoscopies should be considered in these patients.